LC-MS based metabolomics identification of natural metabolites against Fusarium oxysporum - Yang, Wenjuan; Tang, Sidi; Xu, Rubing; Zhang, Lu; Zhou, Zihao; Yang, Yong; Li, Yanyan; Xiang, Haibo (Frontiers in Plant Science, 2024)
Fusarium is a soil-borne pathogen that poses a serious threat to the quality and yield of hundreds of crops worldwide, particularly tobacco production. Using metabolomics technology, we investigated natural metabolites from disease-conducting soil (DCS) and disease-suppressing soil (DSS) of tobacco rhizosphere as fungicides to control tobacco Fusarium wilt (TFW), which is mainly caused by Fusarium oxysporum.Our preliminary results suggested the antifungal mechanism of these natural metabolites. Metabolomics results showed that the DCS with three different disease grades (G1, G5 and G9 groups) had significantly higher levels of 15, 14 and 233 differential rhizosphere metabolites (DRMs) and significantly lower levels of 72, 152 and 170 DRMs compared to the DSS (G0 group). According to KEGG pathway analysis, these DRMs were found to be enriched in the caffeine metabolism, biosynthesis of phenylpropanoids, galactose metabolism and tyrosine metabolism, etc. Linustatin, scopoletin and phenylpropiolic acid were picked out from these DRMs and found to have suppressive activity against F. oxysporum through correlation analysis and antifungal experiments. The three DRMs showed strong inhibitory effects on the growth and spore germination of F. oxysporum at concentrations of 0.5 mM or higher in each test period. Furthermore, F. oxysporum showed a phobotaxis effect against these three DRMs at concentrations as low as 0.25 mM. Finally, we found that the three DRMs had an inhibitory effect on F. oxysporum by destroying the integrity of the cell membrane and increasing the membrane permeability of F. oxysporum. This study firstly reports the inhibition activity of phenylpropiolic acid and linustatin on F. oxysporum, providing a practical and environmentally friendly method for biocontrol of TFW by using natural fungicides.